The Effect of Capital Structure on Financial Performance In Food And Beverage Manufacturing Subsector Companies Listed on The Indonesia Stock Exchange During The 2022–2024 Period - Sarah Fauziah; Andri Mauludi (PT Keberlanjutan Strategis Indonesia, 2026)
Capital structure is an important factor influencing a company’s financial performance, particularly in food and beverage manufacturing firms, which generally require substantial operational and investment financing. The use of debt that is not managed optimally may reduce the company’s efficiency in generating profits. This study aims to provide empirical evidence on the effect of short-term debt and long-term debt on financial performance, measured by Return on Assets (ROA), as well as to examine the role of firm size as a moderating variable. This research applies panel data regression to food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period, using secondary data in the form of annual financial statements. The results indicate that both short-term debt and long-term debt have a negative and significant effect on the companies’ financial performance. This finding suggests that an increase in corporate liabilities tends to reduce the company’s efficiency in utilizing its assets to generate profits. Firm size has a positive but insignificant effect on ROA. In addition, the moderation test shows that firm size is able to moderate the effect of short-term debt on financial performance, but is unable to moderate the effect of long-term debt on financial performance. It is expected that this study will serve as a consideration for company management in formulating a more optimal capital structure policy.